Estimativa da sulfatação total na atmosfera em diferentes regiões do Ceará - Girão, Solange Maria Bastos (2007)
The present work is about the study of the values of concentration of total sulfation that had contributed to determine the category of corrosivity estimated of the atmosphere of the State of the Ceará. The estimate of the Total Sulfation in the Atmosphere followed the general lines of Norm NBR 6921 – Total Sulfation in the Atmosphere - Determination of the tax by the Lead Dioxide Candle Method. The presented data of sulfation had been gotten through passive samplers installed in the stations of study of atmospheric corrosion COFECO, NUTEC, Camocim, Barra da Sucatinga, Pecém, Itaiçaba, Maracanaú, Limoeiro do Norte and Quixadá, where the collection of the pollutant was carried through monthly. From the sulfation data, added to the data of chlorides and time of humid surface, the atmosphere of these stations was classified partially how much its corrosivity according to Norm NBR 14643 (2001) - Classification of the Atmosphere Corrosivity. As a result COFECO station presented category of superior corrosivity the 5, highest corrosivity. The stations Camocim and Barra da Sucatinga, category of corrosivity 5, high corrosivity. While the stations Limoeiro do Norte, Quixadá, Itaiçaba, Pecém, Maracanaú and NUTEC, category of corrosivity 3, average corrosivity